(untitled) (Olhares, 2020)
This article reflects on the pandemic of COVID-19 and some of its consequences on education, such as the schools shutdown, the use of online teaching and the gradual return to face-to-face classes. In this obscure scenario, art is thought as a tool that contributes to the sheltering and the sense of belonging of students in the scholar environment and a way to prevent further school dropout.